Knowledge of Sarcopenia and Associated Factors Among the Malaysian General Public: A Cross-sectional Study - Soon Lean Keng; Noor Hazlisa Che Seman; K.Mangaikresh Krishnan; Chook Jack Bee; Joyce Leong Whye Sook; Siti Fairuz Ismail; Ooi Pei Boon; Peh Suat Cheng (Korean Society for Preventive Medicine, 2023)
Objectives Sarcopenia has emerged as a significant aging-related disease that affects many facets of societal-level and patient-level public health. This study analysed knowledge of sarcopenia and associated socio-demographic factors among the general public of Malaysia in order to effectively improve its prevention and countermeasures. Methods A cross-sectional online survey was conducted in Selangor, Malaysia, using Google Forms among 202 Malaysian adults from January 1, 2021 to March 31, 2021. Descriptive statistics were used to analyse the socio-demographic characteristics and knowledge scores. The continuous variables were evaluated using the independent t-test, Mann-Whitney test, and one-way analysis of variance test. The Spearman correlation coefficient was employed to determine the correlation between socio-demographic characteristics and knowledge score levels. Results The final analysis included 202 participants. The mean±standard deviation age was 49.03±12.65. Only 6.9% of participants had good knowledge of sarcopenia and were aware of sarcopenia's characteristics, consequences, and treatments. Post-hoc comparisons using the Dunnett T3 test showed statistical significance in mean knowledge score and age group (p=0.011) and education level (p≤0.001). The Mann-Whitney test revealed that gender (p=0.026) and current smoking status (p=0.023) significantly influenced knowledge scores. Conclusions The general public's knowledge of sarcopenia was found to be poor to moderate and associated with age and education status. Therefore, education and interventions by policymakers and healthcare professionals to improve public knowledge of sarcopenia in Malaysia are needed.